Evaluasi Pembelajaran Sekolah Dasar (SD) Berbasis Pendidikan Karakter dan Multikultural - Ivo Basri (Jurnal Ilmiah Sekolah Dasar, 2017)
Learning evaluation is the overarching concept which both depends upon measurements and assessment to make a composite judgment or decision. Character education and multicultural learning evaluation in elementary school (SD) adjusted with level thinking  of the children in  elementary school. Where there are still in early stages of the  abstract. Character education is a system of cultivation of character values to the  school community, which includes knowledge, awareness or volition, and actions to implement these values, both of the Almighty God (Almighty), ourselves, others, the environment, and national so that the perfect man to be human. While, indeed  multicultural education becomes an integral part in all levels of education. Therefore  the value investment multicultural ideally applied in all of subjects at formal education